Gestão de estoques: estudo aplicado em uma loja de moto peças localizada na cidade de Assú-RN - Soares, Larissa Almeida (Universidade Federal Rural do Semi-Árido, 2019)
Inventory management is one of the prominent areas within an institution, due to inventory items that are inert for long periods, and the risk of having obsolete goods, which retain a high capital investment of the same. This research had as objective to analyze the management of the stock by means of the curve ABC, in a segment motorcycle parts company, located in the city of Assú in the interior of Rio Grande do Norte. We carried out the pieces in stock, trying to group them and classify them as to their importance. The study was conducted from November 2018 to February 2019, where there was contact with the manager of the company, and later, technical visits the same. Data collection was performed through the use of the software Sisbar and photographic records of the installation. Within the stock control study, the safety stock tool and resupply point were used by calculating the lead time, the normal distribution and the standard deviation. For a given product, with higher output flow, the safety stock and resupply point were used. It was verified that for this item its security stock is of 68 products and its resupply point of 92 items. With the results acquired at the end of this analysis, one can observe the items of greater importance for the company, presenting to the manager what items deserve caution.
Artigo Acadêmico
Keywords: Controle de estoques; Curva ABC; Estoque de segurança; Ponto de ressuprimento; Inventory control; ABC curve; Safety stock; Resupply point; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA